Pengaruh Lingkungan Sekolah Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam (PAI): (Studi Kasus Di SMP Pasundan 3 Cimahi) - Irfan Setia Permana W; Arlin Annisa Ramdaniah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
The school environment is the second major educational environment after family. Students, administrator teachers, counselors live together and carry out the educational process in an organized and planned manner. The problem examined in this study is how the influence of the environment situation of Pasundan 3 Cimahi Middle School on student learning outcomes in Islamic Religious Education subjects. The location in this study is Pasundan 3 Cimahi Middle School. The purpose of this study is to find out how much influence the school environment has on learning outcomes in Islamic Religious Education subjects. The sample in this study were 33 students from all students with details of 11 students from class VII, 11 students from class VIII and 11 students from class IX. To obtain valid data, researchers used data collection tools such as questionnaires, documentation and observation. As for data analysis, researchers used quantitative methods using statistical formulas namely Mean (average), Standard Deviation (SD), TSR, then product moment correlation and coefficient of determination. Based on the results of hypothesis testing that the school environment can influence student learning outcomes. This can be seen from the value of "r" of 0.539 with a significance level of 0.355 (5%) and 0.456 (1%). Thus the "r" count 0.539 is greater than the "r" table both at the significance of 5% and 1%. Then the calculation of the coefficient of determination obtained R2 0.290. Meaning 29% student learning outcomes are influenced by the school environment. So the alternative hypothesis Ha is accepted and Ho is rejected. This means that there is a significant influence between the school environment on student learning outcomes in Islamic Religious Education subjects at SMP Pasundan 3 Cimahi.